Bacteriocin production enhancing mechanism of Lactiplantibacillus paraplantarum RX-8 response to Wickerhamomyces anomalus Y-5 by transcriptomic and proteomic analyses - Nie, Rong; Zhu, Zekang; Qi, Yanwei; Wang, Zhao; Sun, Haoxuan; Liu, Guorong (Frontiers in Microbiology, 2023)
Plantaricin is a kind of bacteriocin with broad-spectrum antibacterial activity on several food pathogen and spoilage microorganisms, showing potential in biopreservation applications. However, the low yield of plantaricin limits its industrialization. In this study, it was found that the co-culture of Wickerhamomyces anomalus Y-5 and L. paraplantarum RX-8 could enhance plantaricin production. To investigate the response of L. paraplantarum RX-8 facing W. anomalus Y-5 and understand the mechanisms activated when increasing plantaricin yield, comparative transcriptomics and proteomics of L. paraplantarum RX-8 were performed in mono-culture and co-culture. The results showed that different genes and proteins in the PTS system were improved and enhanced the uptake of certain sugars; the key enzyme activity in glycolysis was increased with the promotion of energy production; arginine biosynthesis was down-regulated to increase glutamate mechanism, and then promoted plantaricin yield; and ith the expression of several genes/proteins related to purine metabolism were down-regulated and those related to pyrimidine metabolism were up-regulated. Meanwhile, the increase in the activity of the plantaricin synthesis regulation gene plnABCDEF under co-culture indicated that the PlnA-mediated quorum sensing system took part in the response mechanism of L. paraplantarum RX-8. However, the absence of AI-2 did not influence the inducing effect on plantaricin production. Mannose, galactose and glutamate were critical metabolites and significantly simulate plantaricin production (P<0.05). In summary, the findings provided new insights into the interaction between bacteriocin-inducing and bacteriocin-producing microorganisms, which may serve as a basis for further research into the detailed mechanism.